Evaluating an adapted reverse categorisation task to assess cognitive flexibility in young children with Down syndrome. - Van Deusen, K.; Prince, M. A.; Thurman, A. J.; Esbensen, A. J.; Patel, L. R.; Abbeduto, L.; Walsh, M. M.; Daunhauer, L. A.; Feigles, R. T.; Fidler, D. J. (Journal of Intellectual Disability Research, 2023)
Background: Accurate measurement of cognitive skills is necessary to advance both developmental and intervention science for individuals with Down syndrome (DS). This study evaluated the feasibility, developmental sensitivity and preliminary reliability of a reverse categorisation measure designed to assess cognitive flexibility in young children with DS. Methods: Seventy‐two children with DS ages 2.5–8 years completed an adapted version of a reverse categorisation task. Twenty‐eight of the participants were assessed again 2 weeks later for retest reliability. Results: This adapted measure demonstrated adequate feasibility and developmental sensitivity, and preliminary evidence for test–retest reliability when administered to children with DS in this age range. Conclusions: This adapted reverse categorisation measure may be useful for future developmental and treatment studies that target early foundations of cognitive flexibility in young children with DS. Additional recommendations for use of this measure are discussed.